Improving Civics Learning Outcomes through the Quantum Learning Model for Grade XI Students of SMA Negeri 7 Pangkep - Muslina, Muslina; Nur, Jumiati; Syahrir, Mudalifah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine the teacher’s activities, students’ activities, and learning outcomes in Civics Education (PPKn) through the implementation of the Quantum Learning model in Grade XI students of SMA Negeri 7 Pangkep. The research employed a Classroom Action Research (CAR) design with two cycles, each consisting of the planning, implementation, observation, and reflection stages. Data were collected through observation, learning outcome tests, and documentation. The results showed a significant improvement in teacher activities, student activities, and student learning outcomes from cycle I to cycle II. Teacher activity increased from 65.27% (good) to 87.5% (very good), student activity improved from the good category to very good, while learning mastery increased from 53.33% in the pre-cycle to 85.45% in cycle II. These findings confirm that the Quantum Learning model is effective in improving Civics Education learning outcomes.